Value chain analysis of Safflower – A study in Vikarabad district of Telangana: Value chain analysis of Safflower – A study in Vikarabad district of Telangana - G SOWMYA; K SRAVANTHI (Journal of Oilseeds Research, 2023)
The study investigated the movement of safflower seeds from farmer to consumers and also the costs and returns incurred by the safflower farmers. Tracking the movement of safflower from farm to consumer will identify all the stakeholders involved in the value chain. For accomplishing these objectives primary data required was collected from the farmers and also the other stakeholders from the study area with the help of schedules. Value chain analysis identified that the main activities included input logistics, production, marketing and processing. Input logistics includes the activities that involve the movement of the inputs like seeds, fertilizers and pesticides from suppliers to farmers. The data obtained was analysed and it indicated that the value addition to safflower was restricted to marketing onty two products, refined and cold pressed safflower oil, while there was scope for many other products like dyes, cosmetics and food colouring products. Some possible strategies to increase the value chain in this crop are discussed.